Seismic noise as a window into volcanic unrest: observations from Ruapehu, New Zealand, in 2022 - Mustafa Almassri; Oliver D. Lamb; Stuart Mead; Georg F. Zellmer (Bulletin of Volcanology, 2026)
Detecting subsurface changes during volcanic unrest remains challenging when surface manifestations are weak or absent. Between March and July 2022, Ruapehu volcano (New Zealand) experienced heightened seismicity, volcanic tremor, and crater lake heating, yet no eruption occurred. To monitor temporal variations in the subsurface elastic properties during this unrest episode, we estimated relative velocity changes ( $$\varvec{dv/v}$$ d v / v ) from the coda of the correlations using the Moving Window Cross-Spectral (MWCS) method. Our results show spatially heterogeneous changes: a distinct velocity drop occurred on the NE flank, while the NW flank showed no such pattern. The network mean velocity reached $$\varvec{\sim }$$ ∼ −0.26% in the 0.1–0.3 Hz frequency band, corresponding to peak sensitivity to structural changes at depths of $$\varvec{\sim }$$ ∼ 2–6 km. A 20-day temporal lag between the NE flank and summit signals suggests a lateral-to-vertical migration of magmatic fluids toward the vent. Following the unrest, $$\varvec{dv/v}$$ d v / v recovered to background levels as the crater lake cooled. This may indicate a reversible restoration of the edifice’s elastic state and the cessation of volcanic forcing. Although environmental factors were considered, the magnitude and timing of the $$\varvec{dv/v}$$ d v / v variations are more consistent with a primary volcanic driver. This is the first $$\varvec{dv/v}$$ d v / v application at Ruapehu focusing on a non-eruptive unrest episode; it suggests that frequency-dependent depth constraints and spatial localization can effectively monitor magmatic processes in the absence of measurable geodetic deformation. As such, this approach may improve monitoring and risk assessments of volcanic hazards during similar episodes of unrest.

The application of InSAR DEMs for volcanic hazard assessments at Mount Taranaki, New Zealand - Samuel McGowan; Jonathan Procter; Stuart Mead; Gabor Kereszturi (Journal of Volcanology and Geothermal Research, 2026)

Global sensitivity analysis of models for volcanic ash forecasting - Emmy Scott; Melody Whitehead; Stuart Mead; Mark Bebbington; Jonathan Procter (Journal of Volcanology and Geothermal Research, 2025)

Simulation of the 2012 Te Maari debris avalanche: Insight into the failure mechanics and the role of the hydrothermal system - Juliette Vicente; Stuart Mead; Gabor Kereszturi; Craig Miller (Journal of Volcanology and Geothermal Research, 2025)

Modelling and mapping of subsurface nitrate-attenuation index in agricultural landscapes - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne (Journal of Environmental Management, 2025)

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

Approaching the challenge of multi-phase, multi-hazard volcanic impact assessment through the lens of systemic risk: application to Taranaki Mounga - Alana M. Weir; Thomas M. Wilson; Mark S. Bebbington; Sarah Beaven; Teresa Gordon; Craig Campbell-Smart; Stuart Mead; James H. Williams; Roger Fairclough (Natural Hazards, 2024)
Effective volcanic impact and risk assessment underpins effective volcanic disaster risk management. Yet contemporary volcanic risk assessments face a number of challenges, including delineating hazard and impact sequences, and identifying and quantifying systemic risks. A more holistic approach to impact assessment is required, which incorporates the complex, multi-hazard nature of volcanic eruptions and the dynamic nature of vulnerability before, during and after a volcanic event. Addressing this need requires a multidisciplinary, integrated approach, involving scientists and stakeholders to co-develop decision-support tools that are scientifically credible and operationally relevant to provide a foundation for robust, evidence-based risk reduction decisions. This study presents a dynamic, longitudinal impact assessment framework for multi-phase, multi-hazard volcanic events and applies the framework to interdependent critical infrastructure networks in the Taranaki region of Aotearoa New Zealand, where Taranaki Mounga volcano has a high likelihood of producing a multi-phase explosive eruption within the next 50 years. In the framework, multi-phase scenarios temporally alternate multi-hazard footprints with risk reduction opportunities. Thus, direct and cascading impacts and any risk management actions carry through to the next phase of activity. The framework forms a testbed for more targeted mitigation and response planning and allows the investigation of optimal intervention timing for mitigation strategies during an evolving eruption. Using ‘risk management’ scenarios, we find the timing of mitigation intervention to be crucial in reducing disaster losses associated with volcanic activity. This is particularly apparent in indirect, systemic losses that cascade from direct damage to infrastructure assets. This novel, dynamic impact assessment approach addresses the increasing end-user need for impact-based decision-support tools that inform robust response and resilience planning.

Probabilistic volcanic mass flow hazard assessment using statistical surrogates of deterministic simulations - Stuart R. Mead; Jonathan Procter; Mark Bebbington (Computers & Geosciences, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Combining Statistical Design with Deterministic Modelling to Assess the Effect of Site-Specific Factors on the Extent of Landslides - Vincent Lemiale; Carolyn Huston; Stuart Mead; David L. J. Alexander; Paul W. Cleary; Deepak Adhikary; Gary W. Delaney (Rock Mechanics and Rock Engineering, 2022)

A scenario-based risk framework for determining consequences of different failure modes of earth dams - Paul W. Cleary; Mahesh Prakash; Stuart Mead; Vincent Lemiale; Geoff K. Robinson; Fanghong Ye; Sida Ouyang; Xinming Tang (Natural Hazards, 2015)

Determining change points in data completeness for the Holocene eruption record - Stuart Mead; Christina Magill (Bulletin of Volcanology, 2014)